Griqua hymnody: a musical ethnography of Griqua identity through song - Meyer, Chester Aubrey (University of the Free State, 2015)
English: The study presents the hymnodic practises of the Griqua community belonging to the Kranshoek based Griqua Independent Church. The research traces the history of the Griqua and their hymns from eighteenth century missionaries until the spiritual and political work of A.A.S. Le Fleur I in the twentieth century. Issues regarding Griqua identity and the effects of colonisation and apartheid are highlighted and placed within the current South African context. The research and fieldwork further demonstrate that hymnody becomes the manner in which the Griqua community perform their identity as a marginalised community in South Africa. Ethnographic narratives illustrate the true nature of the Griqua hymn as well as the profound effect it has on the communal and personal lives of this community. The distinctive performance practice of these hymns referred to by the Griqua community as lof, played a pivotal part in the formation and sustaining of the twentieth century Griqua ethnic identity and remains a marker of Griqua identity for the followers of Le Fleur today. The study furthermore investigates the role hymnody fulfils in the everyday lives of members as well as the manner in which it attracts new members and retains the Griqua youth. The musical ethnography utilized in this study positions Griqua hymnody as a unique South African expressive culture.

Afrikaans: Die studie bespreek die himnologiese praktyke van die Griekwa gemeenskap wat geafillieer is met die Kranshoek gebaseerde Griekwa Independente Kerk. Die navorsing volg die geskiedenis van die Griekwa en hul kerklied vanaf die agtiende eeuse sendelinge tot die spirituele en politieke werwing van A.A.S. Le Fleur I gedurende die twintigste eeu. Griekwa identiteit word ondersoek teen die agtergrond van kolonialisasie en apartheid en dit word positioneer binne die hedendaagse Suid- Afrikaanse konteks. Die navorsing en veldwerk toon dat himnologie nou as uitdrukkingsmiddel van die Griekwa se identiteit as gemarginaliseerde gemeenskap in Suid-Afrika aangewend word. Die aanwending van n etnografiese narratief illustreer die ware aard van Griekwa himnologie asook die invloed daarvan op die gemeenskaplike en persoonlike lewens van hierdie gemeenskap. Die unieke uitvoeringspraktyk van hierdie kerkliedere word deur die spesifieke gemeenskap beskryf as “lof”. Dit is dan juis die “Griekwa lof” wat ‘n beduidende rol gespeel het in die formasie en volhoubaarheid van die Griekwa etniese identiteit van die twintigste eeu en dit dien steeds as aanduiding van ‘n Griekwa identiteit vir die hedendaagse volgelinge van Le Fleur. Die studie toon verder watter rol himnologie vervul in die alledaagse lewens van lede en hoe dit ook aangewend word om lede te werf en die Griekwa jeug te behou. Die musikale etnografie wat in hierdie studie aangewend word positioneer Griekwa himnologie nou as ‘n unieke ekspressiewe kultuur in Suid- Afrika.
Keywords: Dissertation (M.Mus. (Music))--University of the Free State, 2015; Hymns, Griquas; Griquas -- South Africa -- Ethnic identity; Griquas -- Social life and customs; Church music